Rice Bran Addition to Leaf Compost Can Reduce Radiocesium Concentration and Its Uptake by Crops After the Fukushima Daiichi Nuclear Power Plant Accident. Issue 3 (3rd July 2019) - Moqbal, Mohammad Ismail; Komatsuzaki, Masakazu; Jayasanka, Dikkumburage Jasintha
Abstract: Leaf composting is an essential technique in organic farming; it improves the physicochemical properties of soil such as texture, structure, water-holding capacity, and nutrient content. However, the use of leaf compost is prohibited in the Fukushima and Ibaraki prefectures because large areas of the Fukushima and Ibaraki forests were contaminated by radiocesium ( 134 Cs and 137 Cs) after the Fukushima Daiichi nuclear power plant (FDNPP) accident. We examined the changes in radio Cs concentration and other physicochemical properties in leaf compost made from Ibaraki and Fukushima forest leaves. At the beginning of the composting process, rice bran-treated compost showed 25%–32% lower radio Cs concentration than the leaf-only compost; however, 2 years after composting, the difference in concentration between these treatments had increased to 35%–63%. Moreover, the incorporation of rice bran significantly increased the compost temperature, moisture, electrical conductivity, bulk density, and total nitrogen during the composting process. Plant uptake of radio Cs was significantly lower in rice bran-treated compost than the leaf-only compost at each level of application; furthermore, the levels of soil radio Cs showed a similar trend. Potassium application combined with leaf compost resulted in a significant reduction of radio Cs plant uptake. Our data revealed that adding rice bran to leaves positively affects radio Cs reduction in leaf compost and also reduces its uptake by plants. Our findings may improve the management of leaf composting after the FDNPP accident.